'I don't consider a cup performance; I consider it a test': masculinity and the medicalisation of infertility. Issue 5 (19th December 2015) - Bell, Ann V.
Abstract: Researchers have deemed medicalisation a 'gendered' theory, yet the incorporation of men and masculinity in medicalisation literature is sparse. Recently, however, medicalisation scholarship has begun studying men. This burgeoning literature heavily emphasises sexuality and is beginning to focus on medicalised masculinities in which traits associated with masculinity are deemed a health risk. Such research has demonstrated how masculinities shape men's lived experiences of health, but how does health itself shape masculinity? I explore this question using the case of infertility. Through thirty in‐depth interviews, I find that men use medicine as a way to achieve rather than diminish their sense of masculinity in the feminised context of reproduction. By perpetuating the stereotype that infertility is a woman's problem, the medical establishment has caused men to not necessarily see themselves as infertile. Additionally, even if men do claim the infertility status, they do not perceive it as negative. The legitimating effects of medicalisation objectify the ailment and separate its connection with sexuality. In centring men's voices, the study not only reveals men as active players in the reproductive process, but also incorporates them into understandings of medicalisation.